Rock art handbook : techniques and projects for painting, coloring, and transforming stones - Sarles, Samantha (Fox Chapel Publishing Company, Inc., 2018)
"A guide to how to decorate rocks, utilizing a variety of decorative mediums and articles. Meant for both novices as well as experienced crafters, including a segment on projects to share with children"--